France and the Failure to Modernize Macroeconomic Institutions - Eugene White (Rutgers University, Department of Economics, 1999)
While a great power in the eighteenth century, France fell behind Britain's lead in modernizing her macroeconomic institutions. This paper examines the development of French macroeconomic institutions from the middle ages to the eighteenth century in a comparative framework. Theories of optimal macroeconomic policy and sovereign debt identify the key weaknesses of French institutions that imposed inferior policy choices on the government. Radical reform was blocked by a political economy created by medieval and early modern France. The difficulty experienced by the government in mobilizing resources to fight wars was a key factor contributing to the loss of France's overseas empire in the eighteenth century.
Keywords: E63; N13; 330; France; History; Macroeconomic policy